Development of a measuring channel for low currents integrating on Analog Devices components and Arduino modules for physical experiments - Shlyahov, I.N.; Maslov, N.I.; Karpus, S.H.; Kovalenko, G.D.; Semisalov, I.L.; Kapliy, A.A.; Kiprich, S.K.; Ovchinnik, V.D.; Shulika, M.Yu.; Vasiliev, G.P.; Yalovenko, V.I. (Problems of Atomic Science and Technology, 2022)
The development of low currents measuring channel necessary to ensure the operation of the experimental complex based on a linear electron accelerator with energy of 30 MeV at IHEPNP NSC KIPT for fundamental and applied research on the interaction of high-energy electrons with amorphous and single-crystal structures is described. The channel makes it possible to measure currents of the order of 0.1 nA and less, with an accuracy better than 0.1 %, and is connected to an upper-level computer via the USB interface. Представлено розробку вимірювального каналу малих струмів, необхідного для забезпечення функціонування експериментального комплексу на базі лінійного прискорювача електронів з енергією 30 МеВ ІФВЕЯФ ННЦ ХФТІ для фундаментальних та прикладних досліджень щодо взаємодії електронів високих енергій з аморфними та монокристалічними структурами. Канал дозволяє вимірювати струми порядку 0,1 нА і менше, з точністю не гірше 0,1 %, і має зв’язок з ЕОМ верхнього рівня за інтерфейсом USB.